UNDERGROUND ORGANIZATIONS OF PATRIOTIC YOUTH AND THEIR LIQUIDATION BY THE STATE SECURITY AGENCIES OF THE UKRAINIAN SSR (the second half of the 1950s – first half of the 1970s) - TROFYMOVYCH, Volodymyr; TROFYMOVYCH, Liliya (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The methodological basis of the research is the principles of scientific objectivity, systematicity, verification, and historicism. Both general scientific (analysis, synthesis, generalization) and special historical (historical and comparative, historical and genetic, historical and systemic) methods have been used. The scientific novelty of the research results is determined by the fact that, based on the unpublished archival materials mostly, the activities and liquidation of opposition youth organizations and groups by the state security bodies of the Republic during the period under study have been analysed. Conclusions. The mid-1950s were marked by the emergence of a new stage in the national liberation struggle of the Ukrainian people – the transition to unarmed resistance to the Soviet regime. Having taken advantage of the political thaw, the opposition organizations of patriotic youth emerged: the United Party for the Liberation of Ukraine (1955); the Ukrainian National Front (1964); For Free Ukraine (1965); the Volia Committee (1969); the Organization of Ukrainian Youth of Galicia (1972); the Golden Four (1973), and other underground youth groups. Their participants spoke out against the administrative command pressure and arbitrariness of the communist regime, violations of the rule of law, the implementation of the policy of Russification in Ukraine, fought for civil liberties, the national rights of the Ukrainian people, conducted anti-Soviet agitation, discussed ways of fighting for independent Ukraine, etc. The Republic’s state security organs, guided by the instructions of the party and Soviet bodies, made enormous efforts to expose and eliminate opposition youth organizations and groups, often using extremely harsh sanctions provided for by the Criminal Code. Key words: underground youth organizations and groups, state security bodies of the Ukrainian SSR, Ukrainian nationalists, anti-Soviet activities, arrests.